A rapidly convergent algorithm for computerized synthesis of machine tool gear drives - Siva Prasad, V; Dukkipati, Rao V; Osman, M.O.M (Mechanism and machine theory, 1985)
A complete analysis of all the kinematic versions of a drive having output speeds larger than six and employing the algebraic equations method involves a great deal of manual manipulations. The general theory of composite gear trains could reduce the tedium to some extent, but it could not lead to a general computer algorithm for design synthesis. The present algorithm based on the unified theory provides a computerized method to find the rank of any version in the kinematic merit order. The input data is simplified to that of feeding index exponent values for the applicable versions. The algorithm obviates the tedium of the manual manipulations involved when the algebraic equations method is used instead. Further, the algorithm provides values at a new design optimization point having attractive kinematic features hitherto not obtained. Une analyse complète de toutes les versions cinématiques d'une commande par engrenages à plus de six vitesses de sorties, basée sur les équations algébriques, nécessite un très grand nombre de manipulations manuelles. La théorie générale des trains d'engrenages composés pourrait réduire ce travail fastidieux jusqu 'à un certain point, mais elle ne pourrait pas donner un algorithme informatique général utilisable pour la conception assistée par ordinateur. L'algorithme présenté dans cet article est basé sur une théorie unifiée et il génère des méthodes informatisées permettant de trouver le rang de toute version dans l'ordre du mérite cinématique. En outre, l'algorithme fournit des valeurs à un nouveau point d'optimisation de la conception ayant des caractéristiques cinématiques intéresantes, et qu'on nàurait pas pu obtenir autrement.